Project for Strengthening Pancasila Student Profiles: Phenomenological Study of Students' Moral Education from an Al-Qur'an Perspective - Elvian Mutiara; Mhd Lailan Arqam (At-Tarbiyat, 2024)
Abstract : This study was motivated by the lack of effectiveness of the implementation of P5 for grade 7 students at SMP N 3 Pleret. The purpose of this research is to find out the implementation of P5 7th grade students at SMP N 3 Pleret in accordance with the Qur'anic perspective. The research method used is qualitative with a phenomenological study approach, the researcher directly observes the phenomenon of implementing the Pancasila student profile strengthening project for 7th grade students of SMP N 3 Pleret, the researcher then collects data by observation, interview and documentation. The results of the research found that the application of P5 for 7th grade students at SMP N 3 Pleret with the topic of toga plants fulfills 6 dimensions of P5 and is in line with the Qur'an 1) Faith (QS. Al-Araf: 56); 2) Diversity (QS. Al-Hujurat: 13); 3) mutual cooperation (QS. Al-Hujurat; 13); 4) independence (QS. Al-Mudatssir: 38); 5) critical thinking (QS. Al-Imran: 190); and 6) creativity 9QS. Az-Zumar:9). It is concluded that the project to strengthen the profile of 7th grade Pancasila students at SMP N 3 Pleret can shape student character according to the values of Pancasila and based on the Qur'an. Keywords: Phenomenology, Pancasila Students, Al-Qur'an. Abstrak : Penelitian ini dilatarbelakangi kurangnya kefektifan pelaksanaan P5 siswa kelas 7 di SMP N 3 Pleret. Tujuan penelitin ini untuk mengetahui pelaksanaan P5 siswa kelas 7 di SMP N 3 Pleret sesuai dengan prespektif Al-Qur’an. Metode penelitian yang digunakan ialah kualitatif dengan pendekatan studi fenomenologi, peneliti mengamati langsung fenomena penerapan proyek penguatan profil pelajar Pancasila siswa kelas 7 SMP N 3 Pleret, peneliti lalu melakukann pengambilan data dengan observasi, wawancara dan dokumentasi. Hasil peneltian menemukan adanya penerapan P5 siswa kelas 7 di SMP N 3 Pleret dengan topik tanaman toga memenuhi 6 dimensi P5 dan sejalan dengan Al-Qur’an 1) Keimanan (QS. Al-Araf: 56); 2) Kebhinekaan (QS. Al-Hujurat: 13); 3) gotong royong (QS. Al-Hujurat; 13); 4) kemandirian (QS. Al-Mudatssir:38); 5) Berpikir kritis (QS. Al-Imran: 190); dan 6) Kreativitas 9QS. Az-Zumar:9). Maka disimpulakn bahwa proyek penguatan profil pelajar Pancasila kelas 7 di SMP N 3 Pleret bisa membentuk karakter siswa seusai nilai Pnacasila dan berlandaskan Al-Qur’an. Kata Kunci: Fenomenologi, Pelajar Pancasila, Al-Qur’an.